Implications of mesenchymal stem cells in regenerative medicine. (2nd April 2016) - Kariminekoo, Saber; Movassaghpour, Aliakbar; Rahimzadeh, Amirbahman; Talebi, Mehdi; Shamsasenjan, Karim; Akbarzadeh, Abolfazl
Abstract: Mesenchymal stem cells (MSCs) are a population of multipotent progenitors which reside in bone marrow, fat, and some other tissues and can be isolated from various adult and fetal tissues. Self-renewal potential and multipotency are MSC's hallmarks. They have the capacity of proliferation and differentiation into a variety of cell lineages like osteoblasts, condrocytes, adipocytes, fibroblasts, cardiomyocytes. MSCs can be identified by expression of some surface molecules like CD73, CD90, CD105, and lack of hematopoietic specific markers including CD34, CD45, and HLA-DR. They are hopeful tools for regenerative medicine for repairing injured tissues. Many studies have focused on two significant features of MSC therapy: (I) systemically administered MSCs home to sites of ischemia or injury, and (II) MSCs can modulate T-cell-mediated immunological responses. MSCs express chemokine receptors and ligands involved in cells migration and homing process. MSCs induce immunomedulatory effects on the innate (dendritic cells, monocyte, natural killer cells, and neutrophils) and the adaptive immune system cells (T helper-1, cytotoxic T lymphocyte, and B lymphocyte) by secreting soluble factors like TGF-β, IL-10, IDO, PGE-2, sHLA-G5, or by cell–cell interaction. In this review, we discuss the main applications of mesenchymal stem in Regenerative Medicine and known mechanisms of homing and Immunomodulation of MSCs.